The Impact of COVID-19 Crisis on Stock Markets’ Statistical Complexity - Bogdan Dima; Stefana Maria Dima; Roxana Ioan (Complexity)
The spread of the COVID-19 pandemic has severely impacted all aspects of social and economic life, including the evolution of stock markets. Thus, we advance a methodological framework suitable for assessing 2020 year-long shifts in markets’ statistical complexity, and we apply such framework to ten major international developed or emerging stock markets. Our research reveals that this crisis had considerably altered markets’ evolutionary patterns. The network description of markets’ multivocal transmission of complex responses changed in 2020, European and Asian markets playing a pivotal role. Nevertheless, an important regional and time heterogeneity emerges. In addition, we find that the total number of worldwide confirmed COVID-19 cases plays a leading role in the changes in markets’ complexity.